Vortex Tube Air Cooling: The Effect on Surface Roughness and Power Consumption in Dry Turning - Zahari, Taha; Hadi, Abdul Salaam; Tuan Mohammad Yusoff, Tuan Ya; S. Y., Phoon; C. F., Tan; M. A., Akiah (Universiti Malaysia Pahang, 2013)

(untitled)
There has been an increase awareness to reduce environmental impact in the last 10 years. The manufacturing industry is striving to reduce environmental impact by introducing new materials with better characteristics, consume less processing power and use less amount of processing coolant. The main objective of this paper is to study the effect of Ranque-Hilsch vortex cooling tube on power consumption and surface roughness quality in turning process when machining mild steel material with coated carbide cutting tool. The machining parameters involved in the experiment are cutting speed, feed rate and depth of cut. The cutting speed is fixed at 160 m/min while the feed rate and the depth of cut are varied. The feed rates used are 0.10, 0.18 and 0.28 mm/rev, while the depth of cut is varied from 1.0 to 4.0 mm. During the machining process, the cutting temperatures are measured using an infrared thermometer and the power consumption measured using a Prova 6830 power and harmonics analyzer. The machined parts surface roughnesses are measured using a surface roughness tester. The results show that cooling using Ranque-Hilsch vortex tube air cooling reduces the cutting temperature, but the power consumption and surface roughness is better under ambient condition except at higher feed rate.